2002
DOI: 10.21236/ada597063
|View full text |Cite
|
Sign up to set email alerts
|

Department of Defense Ecosystem Management Policy Evaluation

Abstract: Public reporting burden for the collection of information is estimated to average 1 hour per response, including the time for reviewing instructions, searching existing data sources, gathering and maintaining the data needed, and completing and reviewing the collection of information. Send comments regarding this burden estimate or any other aspect of this collection of information, including suggestions for reducing this burden, to Washington Headquarters Services, Directorate for Information Operations and R… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 4 publications
0
2
0
Order By: Relevance
“…In short, a systematic speculative investigation of the specific ways a norm can be deemed (spatially) effective beyond the compliance-noncompliance pair remains to be accomplished. It is this gap that is addressed in the next section; to do so we extensively rely on two conceptsnamely, nomotropism and effectiveness-as-operativity -developed by some Italian philosophers of law (Conte, 2000;Di Lucia, 2002Fittipaldi, 2002Fittipaldi, , 2013Lorini, 2020;Passerini Glazel, 2011, 2012.…”
Section: Alternative Paradigms Of Effectivenessmentioning
confidence: 99%
“…In short, a systematic speculative investigation of the specific ways a norm can be deemed (spatially) effective beyond the compliance-noncompliance pair remains to be accomplished. It is this gap that is addressed in the next section; to do so we extensively rely on two conceptsnamely, nomotropism and effectiveness-as-operativity -developed by some Italian philosophers of law (Conte, 2000;Di Lucia, 2002Fittipaldi, 2002Fittipaldi, , 2013Lorini, 2020;Passerini Glazel, 2011, 2012.…”
Section: Alternative Paradigms Of Effectivenessmentioning
confidence: 99%
“…The DoD adopted ecosystem-based management for natural resources as policy in 1996 and then updated that policy in 2011 (DoD Instruction 4715.03). Case-study research completed in 2002 indicated that many challenges exist to implementing ecosystem-based management principles at DoD installations (Fittipaldi and Wuichet 2002). The primary tool for implementing ecosystem-based management is the Integrated Natural Resource Management Plan (INRMP).…”
Section: Review Of Existing Management Practicesmentioning
confidence: 99%